2020
DOI: 10.17221/11/2020-agricecon
|View full text |Cite
|
Sign up to set email alerts
|

Age management as a human resources management strategy with a focus on the primary sector of the Czech Republic

Abstract: Primary sector, especially agricultural companies, have long been struggling with labour shortages and demographic trends as well as with negative age structure of employees. The article, therefore, aims to identify the organisational benefits and strategies of human resource management that will help ensure a generational change in selected agricultural companies in primary sectors. The data was obtained on the basis of quantitative research in 136 companies operating in the primary sector according to the CZ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…Similar results were stated also by Urbancová and Vrabcová (2020) and Rietveld et al (2022). A certain correlation between perceiving motivational factors in forest enterprises with our research is observed.…”
Section: Resultssupporting
confidence: 92%
“…Similar results were stated also by Urbancová and Vrabcová (2020) and Rietveld et al (2022). A certain correlation between perceiving motivational factors in forest enterprises with our research is observed.…”
Section: Resultssupporting
confidence: 92%
“…Harnessing the potential of all workers in the labor market effectively should be an essential strategy for the human resource management of organizations (von Bonsdorff et al, 2018;Birkinshaw et al, 2019). It can be observed that there are some risks for organizations neglecting age-specific human resource management (Fuertes et al, 2013;Joniaková & Blštáková, 2015;Garavaglia et al, 2021).…”
Section: Theoretical Partmentioning
confidence: 99%
“…Current studies focused on the management of agricultural enterprises only partially map selected managerial problems in this sector, and due to technological development and other related trends it is necessary to direct research to the possibilities of innovative potential of employees and its support by managers in relation to company performance. Innovative approaches are partly captured in the study of Urbancová and Vrabcová (2020) who point out the benefits of implementing age management in the agricultural sector of the Czech Republic. Jankelová et al (2017) deal with management of human resources and its readiness for implementation of new roles of human resource professionals.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…The ongoing industrial revolution and current Covid-19 pandemic have pointed out other facts as well; specifically, that in the times of a crisis it is necessary to search for new procedures and innovative so-lutions, sustainable also in the post-crisis period and also reflecting the new conditions in which current agricultural companies operate. These are technological developments (Min et al 2019;Lezoche et al 2020), e-environment, use of social media (Thakur and Chander 2018), demographic structure of employees (Chand and Markova 2019) linked to the limited workforce fund (Lähdesmäki and Suutari 2020), its different views of the working world and approaches to it, way of life, and efforts to balance professional and personal life (Urbancová and Vrabcová 2020), as well as many others. The crisis accelerated adaptation of Industry 4.0 and it appears that smart farming is the way of the future, with the potential of ensuring sustainable agricultural production.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation